Coffee pulp supplementation prior to breeding improves oxidative status without affecting fertility of primiparous ewes - Gutiérrez-Prado, Lizbet K.; Sánchez-Torres-Esqueda, María T.; Salinas-Ríos, Teodulo; Figueroa-Velasco, José L.; Martínez-Aispuro, José A.; Contreras-Caro-Del-Castillo, David A.; Cárdenas-León, Mario; Nava-Cuellar, Cuauhtémoc; Cordero-Mora, José L.; García-Cue, José L. (Revista Colombiana de Ciencias Pecuarias, 2019)
Background: Coffee pulp has a high content of antioxidants capable of modifying the oxidative status in small ruminants. However, high amounts for a prolonged time can reduce fertility. Objective: To determine the effect of two inclusion levels of coffee pulp during estrous synchronization on reproductive variables and oxidative status of primiparous ewes. Methods: Sixty Suffolk x Dorset primiparous ewes were distributed into three treatments in a completely randomized design; T0: (n=20) 1.5 kg balanced diet, Tl: (n=20) 1.5 kg balanced diet and 5% coffee pulp, T2: (n=20) 1.5 kg balanced diet and 10% coffee pulp. Supplementation was given for 16 days before estrus synchronization and until the beginning of the breeding season. A progestogen (CIDR®) was inserted for ll days and a dose of PGF2a was applied two days prior to its withdrawal. Estrus detection started 12 hours after CIDR withdrawal. Blood samples were obtained during the supplementation period to measure oxidative status, antioxidant capacity, glucose and insulin, and up to 9 days after breeding to determine progesterone concentration. Pregnancy diagnosis was performed at 30 and 60 days post-breeding. An analysis of repeated measures of mixed effects and frequency analysis were carried out. Results: Inclusion of coffee pulp for a short period prior to breeding did not affect reproductive parameters, nor progesterone, glucose or insulin concentrations (p>0.05); however, antioxidant capacity increased, while lipid oxidation showed an opposite trend (p<0.05). Conclusion: Inclusion of up to 10% coffee pulp in the diet of ewe lambs for 16 days prior to breeding improves oxidative status without causing adverse effects on pregnancy, estrus or prolificacy.